Psychosocial factors influencing aggressive driving among commercial and private automobile drivers in Lagos metropolis (2012)
Using 300 purposively selected private and commercial automobile drivers in Lagos, Nigeria as participants and with a combination of FGD, interview and questionnaire. The study investigated the influence of psychosocial factors such as (locus of control, age, years of driving experience, marital status and educational status) on aggressive behavior among the drivers based on the frustration - aggression hypothesis. Given the chaotic traffic situation in Lagos, premise was that the aggressive instincts in human beings would be more pronounced among the drivers thereby negatively affecting their behavior. Result showed that commercial drivers were significantly higher on aggressive driving behavior. Younger drivers were more aggressive than older ones. Aggressiveness was attributed to other factors in the environment other than the drivers themselves. The need for training of drivers in proper and acceptable way of driving within their cultural context was emphasized.